2020
DOI: 10.1111/jscm.12223
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Absorptive Capacity in Three Product Development Strategies

Abstract: This study develops and tests theory about different forms of absorptive capacity that support radical, differentiation and imitation product development strategies. Absorptive capacity theory provides a generalized explanation for how firms exploit their embeddedness in relationships with buyers and suppliers. We develop and test theory that relates combinations of four components of absorptive capacity (R&D capability, product development capability, cooperative embeddedness, and competitive embeddedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…While many of the articles in this review did not include any control variables, we found several others that did. For example, several scholars include firm size (e.g., Bag et al, 2020; Camisón & López, 2010; Camisón & Puig‐Denia, 2016; Dubey et al, 2021; Ehrgott et al, 2013; Kristal et al, 2010; Mitrega et al, 2017; Shafiq et al, 2020) and firm age (e.g., Bag et al, 2020; Bag, Dhamija, et al, 2021; Camisón & López, 2010; Camisón & Puig‐Denia, 2016; Mitrega et al, 2017; Skilton et al, 2020) in their models based on the rationale that firms with more revenue and/or employees have greater access to resources and older firms have a greater accumulation of resources. When assessing the capabilities‐performance relationship, researchers can enhance the validity of research and minimize the potential confounding effects by including relevant, theoretically meaningful control variables beyond the frequently included controls mentioned in this review.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…While many of the articles in this review did not include any control variables, we found several others that did. For example, several scholars include firm size (e.g., Bag et al, 2020; Camisón & López, 2010; Camisón & Puig‐Denia, 2016; Dubey et al, 2021; Ehrgott et al, 2013; Kristal et al, 2010; Mitrega et al, 2017; Shafiq et al, 2020) and firm age (e.g., Bag et al, 2020; Bag, Dhamija, et al, 2021; Camisón & López, 2010; Camisón & Puig‐Denia, 2016; Mitrega et al, 2017; Skilton et al, 2020) in their models based on the rationale that firms with more revenue and/or employees have greater access to resources and older firms have a greater accumulation of resources. When assessing the capabilities‐performance relationship, researchers can enhance the validity of research and minimize the potential confounding effects by including relevant, theoretically meaningful control variables beyond the frequently included controls mentioned in this review.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Skilton et al. (2020) extend the theory of competition network, contending that firms’ exposure to competitive networks and their network positions determine the amount of knowledge and other resources firms can access. Specifically, firms’ central position in the competition network and the exposure to diverse competitive ties provide firms with competitive information, which is a valuable resource in obtaining competitive advantages.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Second, this study extends the social network theory by examining antecedents to an entry decision into a new collaboration network in the healthcare setting. Lastly, to the best of our knowledge, this study is one of the first to examine competition network characteristics (Skilton & Bernardes, 2015;Skilton et al, 2020) in relation to network entry decisions. As such, we expand the scope of scholarship on competition networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications for the extended supply chain network are still poorly understood. This is especially true if we consider the supply network as a complex adaptive system (Choi et al 2001; Pathak et al 2007; Nair et al 2009; Skilton et al 2020) in that suppliers, as adaptive agents, learn as they respond to changes in the environment. A financial squeeze from the buyer firm could cause complex nonbinary and nonlinear reactions as it propagates through the adaptive agents located at various locations of the supply network (Pathak et al 2007; Bode and Wagner 2015).…”
Section: Introductionmentioning
confidence: 99%